Incidence of pink disease of citrus in Alcon Farm, Davao City - Gentica, Xiohara E. (2008)
The incidence of pink disease in 94 citrus trees at Alcon Farm was monitored weekly from October 2007 to February 2008. Initially, 57 trees (61%) were infected, affecting mostly the trees lateral branches. After cutting off the diseased vegetative parts, incidence dropped drastically to 14% at the 1st week of monitoring, much lesser in the ensuing weeks and rising to 51% at the 17th week. It is surmised that the low rainfall occurrence contributed to the low incidence of the disease during much of the period of study. The continuous occurrence of the disease is speculated to be also due to ants that persistently construct their colonies atop the trees and whose movements may facilitate dissemination of disease propagules within a tree or among trees. The girths of infected lateral branches ranged from less than 3 to 22 cm. Lengths of the infected branches ranged from 18 to 379 cm. recurrence of infection ranged from 1 to 7, mostly 1 to 3, times within the 17-week period. A fungus, suspected to be erythricium sp. was isolated from infected branches. However, tests to demonstrate pathogenic association of the organism to citrus plants were unsuccessful. Thus, this should be the focus of future studies on the malady. Meanwhile, it is recommended that regular inspection be undertaken on the farm, and immediate cutting off of infected branches be conducted to contain disease incidence to manageable levels. It is recommened to burn the cut-off plant debris to minimize sources of inoculum. Removal of ant colonies from trees is also advised as a deterrent against disease recurrence and spread